Perceived stifma: prevalence and related factors among clinically diagnosed Nigerian individuals with epilepsy (2001)
The theoretical model that epilepsy is globally stigmatizing was tested among Nigerian adults. The model suggested relationships among several characteristics (seizure control age at onset of illness, duration of epilepsy, seizure type) depression, neuroticism, social support and perceived stigma. Subjects were 264 adults, 21 to 60 years old clinically diagnosed epilepsy. Using both correlational analysis of variables and a hierarchical multiple regression analysis. results of the study suggest that Nigerian individuals with epilepsy felt seriously stigmatized by the illness. Five variables: poor seizure control duration of epilepsy, depression, neuroticism and social supports were related to stigma. However depression and social support best predicted perception of stigma.